Conceptions Of Reason And Revelation In Discourses Mu'tazilah, Asya'riyah, And Maturidiyah (Samarkhan And Bukhara) - Nurhuda, Abid (Islamadina : Jurnal Pemikiran Islam, 2024)
Humans are the most perfect creatures of Allah, and they try their best to achieve the highest degree of piety, either through knowledge initiated by reason or by carrying out obligations initiated by revelation, although in the process it gives rise to heated debate as to which one dominates more, between reason and revelation so that various theological discourses emerged in Islam. So this research aims to describe the concept of reason and revelation in Mu'tazilah, Asya'riyah, and Maturidiyah (Samarkhan and Bukhara) discourses. The method used is qualitative with a literature study approach technique and then concluded descriptively. The results of the research show that the conception of reason and revelation in each school is different, they have their intensity, where the intensity of the use of reason is dominated by the Mu'tazilah school which places reason in the highest position, followed by the next school is the Maturidah Samarkand, then continued by the next school, namely the Maturidiah Bukhara and finally is the Asy'ariah school which is dominated by God's revelation while reason is given the smallest portion compared to the previous three schools.